Natural Farming Network with Khok Nong Na and Water Bank for Sustainable Agriculture in Surin Province - Wattanasin, Phra Maha Suwira; Congkrarian, Ekaphot (Journal of Dhamma for Life, 2025)
This research aims to (1) analyze the challenges of sustainable agriculture through the lens of the Khok Nong Na model implemented by the Natural Agriculture Network in Surin Province; (2) study the water banking system as managed by this network; and (3) investigate the socio-environmental impacts resulting from the implementation of water banks via the Khok Nong Na model within the same context. A qualitative research methodology was employed, using in-depth interviews with a total of 20 key informants across four distinct groups: (1) farmers who participated in the Khok Nong Na project, (2) core members of the Surin Natural Agriculture Network, (3) local community leaders and administrative officials, and (4) Buddhist monks who serve as spiritual leaders within the network. The conceptual frameworks guiding this study include: the theory of sustainable agriculture, the philosophy of sufficiency economy, the theory of water banking, social network theory, and the framework of sustainable development. This study employed a qualitative research methodology, utilizing in-depth interviews and focus group discussions. A total of 20 participants were selected, comprising two buddhist monks, forms of data collection across four key stakeholder groups are 1) farmers participating in the Khok Nong Na project 2) core leaders of the Natural Agriculture Network in Surin Province 3) community and local administrative leaders, and 4) Buddhist monks serving as intellectual and spiritual leaders. Findings from extensive fieldwork and data collection in Surin Province reveal that the Khok Nong Na and underground water bank initiatives are not merely technical innovations in water and land management. Rather, they represent a structural transformation of local livelihood systems, production processes, and social relations—particularly in communities that have historically faced drought, poverty, and dependency on vulnerable external economic systems. The discussion of results can be framed around three major dimensions: the eco-economic dimension, the community-based knowledge management dimension, and the social network management dimension for sustainability. The study highlights the interconnection between sustainable agriculture, the philosophy of sufficiency economy, and water bank management through the Khok Nong Na approach; the collective power of social networks in driving forward these innovations; and the alignment of these practices with the broader goals of sustainable development.